Methionine adenosyltransferase I/III deficiency: beyond the central nervous system manifestations - Nashabat M; Al-Khenaizan S; Alfadhel M (Dove Medical Press, 2018)
Marwan Nashabat,1 Sultan Al-Khenaizan,2 Majid Alfadhel1 1King Abdullah International Medical Research Centre, King Saud bin Abdulaziz University for Health Sciences, Division of Genetics, Department of Pediatrics, King Abdulaziz Medical City, Ministry of National Guard-Health Affairs (NGHA), Riyadh, Saudi Arabia; 2Department of Dermatology, King Abdullah International Medical Research Center, King Saud bin Abdulaziz University for Health Sciences, King Abdulaziz Medical City, Ministry of National Guard-Health Affairs (NGHA), Riyadh, Saudi Arabia Abstract: Methionine adenosyltransferase (MAT) I/III deficiency (OMIM # 250850) is caused by a mutation in MAT1A, which encodes the two hepatic MAT isozymes I and III. With the implementation of newborn screening program to discover hypermethioninemia due to cystathionine beta-synthase deficiency, more cases are being discovered. While the majority of patients are asymptomatic, some might have central nervous system (CNS) and extra-CNS manifestations. Although neurologic manifestations and demyelination have been correlated to MAT deficiency in many reported cases, none of the previous reports focused on extra-CNS manifestations associated with the disease. This is a retrospective chart review for a 40-month-old patient with confirmed diagnosis of MAT deficiency. He was found to have a novel homozygous disease-causing variant in MAT1A (NM_000429.2) c.1081G>T (p.Val361Phe). Interestingly, our patient had an unexplained zinc and iron deficiency in addition to mild speech delay. We reviewed the literature and summarized all the reported extra-CNS manifestations. In conclusion, MAT deficiency patients should be thoroughly investigated to check for CNS and extra-CNS manifestations associated with the disease. Keeping in consideration the challenge of assuming correlation, a scrutinized look at extra-CNS manifestations and their course with time might pave the way to understanding the pathophysiology of the disease and MAT1A function. Keywords: MAT1A, methionine adenosyltransferase, S-adenosyl methionine, central nervous system